Injury prevalence, types and anatomical localizations in elite football players - Akalın, Tevfik Cem; Göktepe, Mehmet; Gümüş, Mustafa; Gökdemir, Kadir; Çıplak, Mustafa Ertuğrul; Emektar, Bilal (Progress in Nutrition, 2020)
Study Objectives: In this study, it was aimed to evaluate the prevalence, types, and anatomical localization of elite football players’ injuries in one season. Methods: The participants of the study are 50 professional male footballers playing in Professional Leagues of Turkish Football Federation with a mean age of 20-29 (25.4±3.1) with 12.67±3.72 years of experience in football. The data collection followed the international consensus statement on procedures for epidemiologic studies of football injuries recommended by FIFA and UEFA. In this study, the contact person collected the date of injury, mechanisms of injury, body area injured, injured structure, diagnosis, severity, minute of match or training results, and time-off (days) for each player together with the sports medical history of the players. Data were collected and analyzed. Results: When the injury profile of the players was considered, it was determined that 34 (68%) players were injured once, nine players (18%) were injured for the second time, and a total of 50 players had 43 injuries in a season. The highest prevalence of injured players was observed in midfielders with 16 (37.2%) and the lowest in goalkeepers with four players (9.3%). In terms of anatomical location, more injuries were observed in the lower extremity and joint and muscle injuries. The most frequently observed types of injuries are sprain, muscle laceration, partial muscle tear, local degeneration, and crush respectively. Conclusion: This study is thought to be a potentially valuable tool for understanding the events that lead to injuries in football by examining some of the factors that affect the injury process of professional soccer players and identifying the types of injuries and their anatomical localization.